Impact of the 2014 to 2016 economic crisis on the beta coefficient of the Brazilian stock market - Nonato, Vinícius Luís de Souza (2020)
Empirical studies have found evidence that the market risk, or market beta, tends to increase in crisis periods. Given the Brazilian economic crisis from 2014 to 2016, this paper investigates whether this crisis had a significant impact on the market risk of the Brazilian firms with stocks negotiated at the Brazilian stock market, Brasil, Bolsa, Balcão (B3). For this, we estimated the trajectory of the beta of a portfolio of stocks traded on B3 for the period from February 2010 to December 2018, considering a conditional CAPM with the dynamics of beta given by a stochastic process combined with conditioning variables related to the economic cycle. We found evidence that the portfolio beta had an increase by January 2015, and only returned to values of the pre-crisis period by March 2018. This evidence is aligned with results found in the international literature and has important implications in terms of risk management.